Multistrain Probiotics Alleviate Diarrhea by Modulating Microbiome-Derived Metabolites and Serotonin Pathway - Jin-Ju Jeong; Yoo-Jeong Jin; Raja Ganesan; Hee Jin Park; Byeong Hyun Min; Min Kyo Jeong; Sang Jun Yoon; Mi Ran Choi; Satya Priya Sharma; You Jin Jang; Uigi Min; Jong-Hyun Lim; et al. (Probiotics and Antimicrobial Proteins, 2025)
Diarrhea, a common gastrointestinal symptom in health problems, is highly associated with gut dysbiosis. The purpose of this study is to demonstrate the effect of multistrain probiotics (Sensi-Biome) on diarrhea from the perspective of the microbiome-neuron axis. Sensi-Biome ( Lactiplantibacillus plantarum , Bifidobacterium animalis subsp. lactis , Lactobacillus acidophilus , Streptococcus thermophilus , Bifidobacterium bifidum , and Lactococcus lactis ) was administered in a 4% acetic acid–induced diarrhea rat model at concentrations of 1 × 10 8 (G1), 1 × 10 9 (G2), and 1 × 10 10 CFU/0.5 mL (G3). Diarrhea-related parameters, inflammation-related cytokines, and stool microbiota analysis by 16S rRNA were evaluated. A targeted and untargeted metabolomics approach was used to analyze the cecum samples using liquid chromatography and orbitrap mass spectrometry. The stool moisture content ( p < 0.001), intestinal movement rate ( p < 0.05), and pH ( p < 0.05) were significantly recovered in G3. Serotonin levels were decreased in the multistrain probiotics groups. The inflammatory cytokines, serotonin, and tryptophan hydroxylase expression were improved in the Sensi-Biome groups. At the phylum level, Sensi-Biome showed the highest relative abundance of Firmicutes . Short-chain fatty acids including butyrate, iso-butyrate, propionate, and iso-valeric acid were significantly modified in the Sensi-Biome groups. Equol and oleamide were significantly improved in the multistrain probiotics groups. In conclusion, Sensi-Biome effectively controls diarrhea by modulating metabolites and the serotonin pathway.

Consumer-driven characterization of healing foods using Q methodology and Q based sorting - Ki-Beom Song; Sébastien Lê; Haeng-Ran Kim; Seon-Mi Yoo; Min-Sook Kang; Han-Na Chu; In-Seon Hwang; Jae-Hee Hong (Food Quality and Preference, 2024)

Characterization and miRNA-mediated posttranscriptional regulation of vitelline membrane outer layer protein I in the adult chicken oviduct - Sang In Lee; Mi-Ran Ji; Ye-Jin Jang; Mi-hyang Jeon; Jeom Sun Kim; Jin-Ki Park; Ik-Soo Jeon; Sung June Byun (In Vitro Cellular & Developmental Biology - Animal, 2015)

Role of vacuolating cytotoxin VacA and cytotoxin-associated antigen CagA of Helicobacter pylori in the progression of gastric cancer - Mi-Ran Ki; Meeyul Hwang; Ah-Young Kim; Eun-Mi Lee; Eun-Joo Lee; Myeong-Mi Lee; Soo-Eun Sung; Sang-Hyeob Kim; Hye Seung Lee; Kyu-Shik Jeong (Molecular and Cellular Biochemistry, 2014)

ENA-A actimineral resource A extends lifespan associated with antioxidant mechanism in SMP30 knockout mice - Jung-Youn Han; Meeyul Hwang; Sung-Yong Hwa; Jin-Kyu Park; Mi-Ran Ki; Il-Hwa Hong; Ah-Young Kim; Eun-Mi Lee; Eun-Joo Lee; Chang-Woo Min; Kyung-Ku Kang; Myeong-Mi Lee; et al. (Molecular and Cellular Biochemistry, 2014)

The Protective Effect of ENA Actimineral Resource A on CCl4-Induced Liver Injury in Rats - Il-Hwa Hong; Hoon Ji; Sung-Yong Hwa; Won-Il Jeong; Da-Hee Jeong; Sun-Hee Do; Ji-Min Kim; Mi-Ran Ki; Jin-Kyu Park; Moon-Jung Goo; Ok-Kyung Hwang; Kyung-Sook Hong; et al. (Marine Biotechnology, 2011)

Effects of bio-active ceramic resources in cutaneous wound healing and the role of TGF-β signaling - Jae-Yong Chung; Sun Hee Do; Won-Il Jeong; Da-Hee Jeong; Sang-Joon Park; Mi-Ran Ki; Dong-Mi Kwak; Soon-Bok Kim; Kyu-Shik Jeong (Molecular and Cellular Biochemistry, 2007)

Up-regulation of Metabotropic glutamate receptor 3 (mGluR3) in rat fibrosis and cirrhosis model of persistent hypoxic condition - Sun Hee Do; Hae-Sun Yun; Won-Il Jeong; Da-Hee Jeong; Mi-Ran Ki; Jae-Yong Chung; Sang-Joon Park; Soon-Bok Kim; Kyu-Shik Jeong (Molecular and Cellular Biochemistry, 2007)

Alcohol-induced bone degradation and its early detection in the alcohol-fed castrated rats - Sun Hee Do; Won Il Jeong; Da Hee Jeong; Mi-Ran Ki; In-Seon Lee; Dong-Mi Kwak; Tae Hwan Kim; Yoo Kyeong Kim; Soon-Bok Kim; Kyu-Shik Jeong (Molecular and Cellular Biochemistry, 2006)